2015
DOI: 10.1260/1369-4332.18.9.1355
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Structural Responses on Artificial Fatigue Crack for Bulb Rib Orthotropic Deck

Abstract: An orthotropic steel deck is quite susceptible to fatigue cracking at its welded joints depending on the structural stiffness, occurrence of high-magnitude cyclic load stress, and complicated geometric details of the welded joints. This study experimentally and numerically investigated the structural behavior of an orthotropic steel deck with bulb ribs. The behavior of the deck was examined, particularly the warped deformations of the developed fatigue cracks and the uniform stress distributions against moving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Due to the advantages such as a light weight, guarantee of high quality, convenience for in-situ assembling process, etc., the orthotropic steel decks have become very frequently used in the construction of bridges [1][2][3]. The orthotropic steel bridge deck is a steel deck system with longitudinal ribs and floor beams to support and resist the applied loads such as vehicles and the dead load, and transfer these loads to the main bridge system, which has different types of structures and stiffness values in the longitudinal and transverse directions [4,5]. Much study has shown that the fatigue failure was one of the major factors in the failure of steel bridges [6][7][8][9], and which is liable to fatigue cracking once placed in service [10].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the advantages such as a light weight, guarantee of high quality, convenience for in-situ assembling process, etc., the orthotropic steel decks have become very frequently used in the construction of bridges [1][2][3]. The orthotropic steel bridge deck is a steel deck system with longitudinal ribs and floor beams to support and resist the applied loads such as vehicles and the dead load, and transfer these loads to the main bridge system, which has different types of structures and stiffness values in the longitudinal and transverse directions [4,5]. Much study has shown that the fatigue failure was one of the major factors in the failure of steel bridges [6][7][8][9], and which is liable to fatigue cracking once placed in service [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly because that not only the effective cross-sectional area of structural components will be reduced but also the fatigue strength of structural components will be deteriorated. Therefore, it becomes a critical issue to assess the long-term performance and safety condition of offshore bridge structures under the coupled effect of corrosion and fatigue (Chen et al, 2012; El Aghoury and Galal, 2014; Feng et al, 2014; Huang et al, 2014; Kainuma et al, 2015; Li et al, 2013, 2015; Yang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…An orthotropic steel bridge deck is a steel deck system with longitudinal ribs and floor beams to support and resist the applied loads such as vehicles and the dead load and transfer these loads to the main bridge system, which has different types of structures and stiffness values in the longitudinal and transverse directions [1]. It has a lighter weight, higher durability, and more rapid construction potential than a traditional concrete bridge deck [2].…”
Section: Introductionmentioning
confidence: 99%